Fostering Autonomy in Flipped Learning: Pre-Class, Active Learning, and Metacognition - Akib, Muhaiminah; Abduh, Amirullah; Sahril, Sahril (Journal of Indonesian Scholars for Social Research, 2025)
This study aims to investigate how the flipped classroom fosters autonomous learning. Employing a qualitative case study approach, the research involved 10 students from the English Education program. The findings identify three key patterns of autonomous learning in the flipped classroom: Pre-class preparation, active learning in class, and metacognitive development. Pre-class preparation allows students to engage with learning materials before class, helping them build foundational knowledge and identify areas for improvement. Active learning in class promotes interaction and critical thinking through collaborative activities, enabling students to apply their pre-class knowledge effectively. Metacognitive Development enhances students' ability to reflect, set learning goals, and regulate their learning strategies. To maximize the benefits of the flipped classroom, educators should design structured pre-class activities, facilitate interactive discussions, and encourage self-regulation strategies. By implementing these practices, students can develop greater autonomy, improve critical thinking skills, and become more engaged in their learning process.